Testing a Disequilibrium Model of Lending Rate Determination : The Case of Malaysia - Scholnick, Barry (IMF Working Papers; Working Paper ;, 1991)
This study examines whether lending rates cleared the market for loans in Malaysia after interest rate liberalization. It is based on a theoretical model in which adverse selection and marginal cost pricing are brought together by the use of a quadratic loss function in the error correction format. This allows for the use of the cointegration methodology. Long-run tests support the model proposed in the paper, while rejecting part of the financial liberalization model. From the short-run results it is concluded that there is a large lag before lending rates respond to exogenous shocks, thus confirming that they do not fully clear the market for loans.